2001
DOI: 10.2105/ajph.91.7.1130
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, betel quid, alcohol, and illicit drug use among 13- to 35-year-olds in I-Lan, rural Taiwan: prevalence and risk factors

Abstract: OBJECTIVES: This study determined the prevalence of and risk factors for substance use among rural Taiwanese. METHODS: We used a survey of a representative sample of 6318 participants aged 13 to 35 years in I-Lan, Taiwan, in 1996 through 1997. RESULTS: Perceived use of illicit drugs by peers, tobacco smoking, betel quid chewing, and male gender were the strongest predictors of illicit drug use. The prevalence of illicit drug use ranged from 0.3% among those who did not use any other substance to 7.1% among tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…In Tyas and Pederson's review [23], age was associated with an increase in smoking prevalence and initiation. Chen and colleagues reported that the mean age of initiation of use any of tobacco, alcohol, or illicit drugs was 16 to 18 years [24]. We observed a similar pattern, except for the decrease in the 7 th grade, which may have been a result of the transition involved in attending a new school.…”
Section: Discussionsupporting
confidence: 78%
“…In Tyas and Pederson's review [23], age was associated with an increase in smoking prevalence and initiation. Chen and colleagues reported that the mean age of initiation of use any of tobacco, alcohol, or illicit drugs was 16 to 18 years [24]. We observed a similar pattern, except for the decrease in the 7 th grade, which may have been a result of the transition involved in attending a new school.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, among the youths, significantly higher prevalence of TS and IDU were found among those aged 20–24 years, which are consistent with the findings of other studies in Bangladesh and elsewhere [5], [16], [17], [38][40]. This may be partially attributed to the traditional and cultural norms in Bangladesh and stress related issues.…”
Section: Discussionsupporting
confidence: 89%
“…It is also noticed that higher education and higher income was protective against PMD and oral cancer. [ 12 23 ] Statistically significant difference was observed between the study population and SES index ( P < 0.01, S). The individuals with less education and low income were more likely to smoke cigarettes, chew tobacco and drink alcohol.…”
Section: Discussionmentioning
confidence: 95%